Territorio, popolazione e risorse strutture produttive nell'economia del mondo romano - Merola, Giovanna Daniela (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2020)
The book is inspired by the reports discussed at the Conference Territorio, popolazione e risorse: strutture produttive nell'economia del mondo romano, organized in Naples, on 26 October 2018; it represents the result of a research project aimed at analysing the economic, political and social evolution of the Italic territory, mainly of Regio I, in Roman times. For this specific geographical-administrative area, we have considered aspects and problems relating to the rural landscape, the forms of production and the role of cities, through the reinterpretation of different types of evidence (primarily literary and documentary sources) on the basis of the theoretical assumption that there is a close correlation between population, resource exploitation and urbanization.